The New Immigrants: A New America. (The Great Courses, 2015)
Here, learn how widespread immigration during the Gilded Age and Progressive Era transformed U.S. society. Delve into the diverse factors underlying immigration, and the perceived threats and social problems posed by immigrants. Observe how society at large reacted to the influx, and grasp the ways in which immigrants fundamentally changed the nation..